A Thermally‐Regenerative Ammonia‐Based Flow Battery for Electrical Energy Recovery from Waste Heat. Issue 8 (15th March 2016) - Zhu, Xiuping; Rahimi, Mohammad; Gorski, Christopher A.; Logan, Bruce
Abstract: Large amounts of low‐grade waste heat (temperatures <130 °C) are released during many industrial, geothermal, and solar‐based processes. Using thermally‐regenerative ammonia solutions, low‐grade thermal energy can be converted to electricity in battery systems. To improve reactor efficiency, a compact, ammonia‐based flow battery (AFB) was developed and tested at different solution concentrations, flow rates, cell pairs, and circuit connections. The AFB achieved a maximum power density of 45 W m −2 (15 kW m −3 ) and an energy density of 1260 Wh manolyte −3, with a thermal energy efficiency of 0.7 % (5 % relative to the Carnot efficiency). The power and energy densities of the AFB were greater than those previously reported for thermoelectrochemical and salinity‐gradient technologies, and the voltage or current could be increased using stacked cells. These results demonstrated that an ammonia‐based flow battery is a promising technology to convert low‐grade thermal energy to electricity. Abstract : Power in numbers : To improve the efficiency of reactors that convert low‐grade waste heat to electricity, a compact ammonia‐based flow battery (AFB) is designed and tested at different solution concentrations, flow rates, cell pairs, and circuit connections. The power and energy densities obtained are greater than those previously reported for thermoelectrochemical and salinity‐gradient technologies, and the voltage or current could be increased using stacked cells. These results demonstrated that an ammonia‐based flow battery is a promising technology to convert low‐grade thermal energy to electricity.